If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9m + -9 = 102 Reorder the terms: -9 + -9m = 102 Solving -9 + -9m = 102 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -9m = 102 + 9 Combine like terms: -9 + 9 = 0 0 + -9m = 102 + 9 -9m = 102 + 9 Combine like terms: 102 + 9 = 111 -9m = 111 Divide each side by '-9'. m = -12.33333333 Simplifying m = -12.33333333
| 587=8x+387 | | -2.8=5.2-2y | | -(-8x+4)+9x= | | -25=5(y-4) | | 4h-6=10n | | -12m-8=70 | | 0.16666666666(12-6x)=5(x+4) | | 0.33333333333(6y-9)=-2y+13 | | 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) | | 28-2x=3x+18 | | .03=.14x+.05-05x | | 8+.09m=90 | | G(2)=5-7+2 | | b/0.8=12.6 | | -6m-13=74 | | 6x^2-54x/x-9•7x/6x | | -7.1=2.9-5y | | 10=1.25*p | | g/3.2=4.7 | | g/2=0.5 | | 4r^2=34-10r | | 4(24)=4(20)+4(4) | | (5x+7)+(4x-18)+(3x+2)=x |